Vegetable Genetic Resources in China - Haiping WANG; Xixiang LI; Jiangping SONG (Horticultural Plant Journal, 2018)
China is recognized as an important region for plant biodiversity based on its vast and historical collection of vegetable germplasm. The aim of this review is to describe the exploration status of vegetable genetic resources in China, including their collection, preservation, evaluation, and utilization. China has established a number of national-level vegetable genetic resources preservation units, including the National Mid-term Genebank for Vegetable Germplasm Resources, the National Germplasm Repository for Vegetatively-Propagated Vegetables, and the National Germplasm Repository for Aquatic Vegetables. In 2015, at least 36 000 accessions were collected and preserved in these units. In the past decade, 44 descriptors and data standards for different species have been published, and most accessions have been evaluated for screening the germplasms for specific important traits such as morphological characteristics, disease resistance, pest resistance, and stress tolerance. Moreover, the genetic diversity and evolution of some vegetable germplasms have been evaluated at the molecular level. Recently, more than 1 000 accessions were distributed to researchers and breeders each year by various means for vegetable research and production. However, additional wild-relative and abroad germplasms from other regions need to be collected and preserved in the units to expand genetic diversity. Furthermore, there is a need to utilize advanced techniques to better understand the background and genetic diversity of a wide range of vegetable genetic resources. This review will provide agricultural scientists’ insights into the genetic diversity in China and provide information on the distribution and potential utilization of these valuable genetic resources. Keywords: vegetable, genetic resource, preservation, evaluation, utilization